Green Accounting, Intellectual Capital, and Dividend Policy On Firm Value in Energy Companies - Frengky Samuel Panjaitan; Arthur Simanjuntak; Januardi Mesakh; Merry Anna Napitupulu (Program Studi Akuntansi Universitas Simalungun, 2026)
This study examines green accounting, intellectual capital, and dividend policy effects on firm value in Indonesian energy companies during 2021-2024. Using multiple linear regression on 48 observations from 12 companies, results show green accounting significantly negatively affects firm value (β = -0.168, p = 0.006), as environmental disclosure signals cost burdens to investors. Intellectual capital demonstrates positive but insignificant influence (β = 0.057, p = 0.230). Dividend policy exhibits significant positive effects (β = 0.324, p = 0.041), signaling financial strength. Simultaneous testing confirms significant collective effects (F = 3.759, p = 0.017), explaining 15.0% of firm value variance. Findings suggest integrated approaches balancing environmental practices, intellectual assets, and shareholder returns optimize value creation in energy sector contexts